2018
DOI: 10.1177/0706743718777392
|View full text |Cite
|
Sign up to set email alerts
|

Movement Disorders Associated With Antipsychotic Medication in People With Schizophrenia: An Overview of Cochrane Reviews and Meta-Analysis

Abstract: Movement disorders associated with antipsychotic medications are relatively common, stigmatising, and potentially disabling. Their prevalence in people with psychosis who are prescribed second-generation antipsychotics (SGAs) is uncertain, as is their level of recognition by clinicinas. We conducted meta-analyses of randomised controlled trials included in the Cochrane Database of Systematic Reviews on schizophrenia and schizophrenia-like psychoses to estimate the prevalence of new-onset dystonia, akathisia, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 70 publications
0
44
0
4
Order By: Relevance
“…They usually present as lip‐smacking, grimacing, puckering, rapid eye blinking and dyskinetic tongue movements, such as protrusion and tongue rolling . TDK can be stigmatising for patients, and adversely affect medication adherence and quality of life, sometimes persisting even after the medication is stopped . It is believed that the pathophysiology of TDK arise from drugs that block central dopamine receptors, although other neurotransmitters may be involved …”
Section: Drug‐induced Tardive Dyskinesiamentioning
confidence: 99%
See 1 more Smart Citation
“…They usually present as lip‐smacking, grimacing, puckering, rapid eye blinking and dyskinetic tongue movements, such as protrusion and tongue rolling . TDK can be stigmatising for patients, and adversely affect medication adherence and quality of life, sometimes persisting even after the medication is stopped . It is believed that the pathophysiology of TDK arise from drugs that block central dopamine receptors, although other neurotransmitters may be involved …”
Section: Drug‐induced Tardive Dyskinesiamentioning
confidence: 99%
“…TDK can be stigmatising for patients, and adversely affect medication adherence and quality of life, sometimes persisting even after the medication is stopped . It is believed that the pathophysiology of TDK arise from drugs that block central dopamine receptors, although other neurotransmitters may be involved …”
Section: Drug‐induced Tardive Dyskinesiamentioning
confidence: 99%
“…Although DIP is less frequent with atypical antipsychotics than typical agents such as haloperidol,17 it is still commonly seen. A recent Cochrane review concluded that DIP has been associated with all second-generation antipsychotics 18…”
Section: Introductionmentioning
confidence: 99%
“…Women were more commonly treated with quetiapine than men (15.8 vs 10.9 per 1000), and the top 4 diagnostic codes associated with quetiapine use were depression, neurotic disorders, bipolar disorder, and sleep disturbances. 12 In the study by Martino and colleagues, 13 we seek to focus attention back on the issue of antipsychotic-induced movement disorders (extrapyramidal symptoms). We hope to highlight that while the prevalence of such movement disorders appears to be lower with the newer antipsychotic medications than with the first-generation agents, the 95% confidence intervals often overlap between new and older agents, and the risk remains substantial.…”
mentioning
confidence: 99%
“…We hope to highlight that while the prevalence of such movement disorders appears to be lower with the newer antipsychotic medications than with the first-generation agents, the 95% confidence intervals often overlap between new and older agents, and the risk remains substantial. 13 Now that antipsychotic medication is used and prescribed by a great number of practitioners to a diverse population of patients, the need for vigilant monitoring has intensified. Many practitioners who began their training in the era of second-generation antipsychotics have not received the same degree of exposure to the recognition and management of antipsychoticinduced movement disorders.…”
mentioning
confidence: 99%